Дифракция H-волн на системе щелей в общей стенке двух параллельно расположенных прямоугольных волноводов - Калиберда, М.Е.; Погарский, С.А. (Радиофизика и радиоастрономия, 2010)
The diffraction of H-modes by a system of
slots in a common wall of two rectangular
waveguides is solved using the operator approach.
The slots are rectangular. The waveguides interaction
behavior, when slot size and position in
waveguide are varied, is investigated. The results
obtained allow to determine the laws of
variation of frequency bands when the structure
under investigation may be used as directional
coupler and power divider. Thus obtained results
were compared with those obtained by other
authors. Решается задача дифракции H-волн на системе щелей в общей стенке двух прямоугольных волноводов с применением операторного метода. Щели имеют прямоугольную форму. Исследован характер взаимодействия волноводов при вариации геометрических размеров щелей и их местоположения в волноводе. Полученные результаты позволяют определить
закономерности изменения полос частот, в пределах которых исследуемая структура может применяться в качестве направленного ответвителя и делителя мощности. Проведено сравнение результатов, полученных данным методом, с результатами, полученными другими авторами. Розв’язується задача дифракції H-хвиль
на системі щілин у спільній стінці двох прямокутних хвилеводів з використанням операторного метода. Щілини мають прямокутну
форму. Досліджено характер взаємодії хвилеводів при варіації геометричних розмірів щілин
та їх положення у хвилеводі. Отримані результати дозволяють визначити закономірності
зміни смуг частот, у межах яких досліджувана структура може використовуватися у якості
спрямованого відгалужувача та подільника
потужності. Виконано порівняння результатів,
отриманих цим методом, з результатами, отриманими іншими авторами. The diffraction of H-modes by a system of
slots in a common wall of two rectangular
waveguides is solved using the operator approach.
The slots are rectangular. The waveguides interaction
behavior, when slot size and position in
waveguide are varied, is investigated. The results
obtained allow to determine the laws of
variation of frequency bands when the structure
under investigation may be used as directional
coupler and power divider. Thus obtained results
were compared with those obtained by other
authors.